Impulsivity in adult male sexual offenders - Dervley, Rebekah (2018)
This research thesis explored impulsivity in adult male sexual offenders. Low self-control and impulsivity are generally associated with criminality (e.g. Andrews & Bonta, 2006), as well as problematic sexual behaviour (Mick & Hollander, 2006). Meta-analyses have provided evidence that self-regulation deficits in sexual offenders are amongst the strongest predictors of recidivism (Hanson, Harris, Scott, & Helmus, 2007; Hanson & Morton-Bourgon, 2005). Researchers have suggested that exploring the construct of impulsivity within forensic populations might help enable identify specific re-offending risks and targets for intervention (Gordon & Egan, 2011; Egan, 2017).